Understanding the Determinants of Gambling-Related Intimate Partner Violence: Perspectives From Women Who Gamble. (October 2022) - O'Mullan, Cathy; Hing, Nerilee; Mainey, Lydia; Nuske, Elaine; Breen, Helen
Rates of intimate partner violence (IPV) victimization are higher among women with a gambling problem. However, women's experiences of this violence, from a gendered perspective, have not been examined. Based on interviews with 24 women, this study explored how problem gambling contributes to IPV against women across three levels of influence. Findings reveal that problem gambling did not directly cause IPV, but interacts where gendered drivers and reinforcers are present to exacerbate this violence. Reducing violence against women with a gambling problem requires a coordinated, integrated multidisciplinary approach targeting different levels of influence.